MicroRNA expression profile of human umbilical vein endothelial cells in response to coxsackievirus A10 infection reveals a potential role of miR-143-3p in maintaining the integrity of the blood–brain barrier - Hu, Yajie; Cui, Fengxian; Wang, Shenglan; Liu, Chen; Zhang, Shengxiong; Wang, Ruiqi; Song, Jie; Zhang, Yunhui (Frontiers in Cellular and Infection Microbiology, 2023)
Coxsackievirus A10 (CV-A10) has been one of the main aetiologies of hand, foot and mouth disease (HFMD) epidemics in recent years and can cause mild to severe illness and even death. Most of these severe and fatal cases were closely associated with neurological impairments, but the potential mechanism of neuropathological injury triggered by CV-A10 infection has not been elucidated. MicroRNAs (miRNAs), implicated in the regulation of gene expression in a post-transcriptional manner, play a vital role in the pathogenesis of various central nervous system (CNS) diseases; therefore, they serve as diagnostic biomarkers and are emerging as novel therapeutic targets for CNS injuries. To gain insights into the CV-A10-induced regulation of host miRNA-processing machinery, we employed high-throughput sequencing to identify differentially expressed miRNAs in CV-A10-infected HUVECs and further analysed the potential functions of these miRNAs during CV-A10 infection. The results showed that CV-A10 infection could induce 189 and 302 significantly differentially expressed miRNAs in HUVECs at 24 hpi and 72 hpi, respectively, compared with the uninfected control. Moreover, the expression of 4 selected miRNAs and their relevant mRNAs was determined to verify the sequencing data by RT‒qPCR methods. After that, gene target prediction and functional annotation revealed that the targets of these dysregulated miRNAs were mostly enriched in cell proliferation, signal transduction, cAMP signalling pathway, cellular response to interleukin-6, ventral spinal cord interneuron differentiation, negative regulation of glial cell differentiation, neuron migration, positive regulation of neuron projection development, etc., which were primarily involved in the processes of basic physiology, host immunity and neurological impairments and further reflected vital regulatory roles of miRNA in viral pathogenicity. Finally, the construction of a miRNA-regulated network also suggested that the complex regulatory mechanisms mediated by miRNAs might be involved in viral pathogenesis and virus‒host interactions during CV-A10 infection. Furthermore, among these dysregulated miRNAs, miR-143-3p was demonstrated to be involved in the maintenance of BBB integrity.